High-sensitivity cardiac troponin T and N-terminal b-type natriuretic propeptide are associated with cardiac and all-cause mortality in older adults – A population-based ten-year follow-up study - Heikkilä, Elisa; Katajamäki, Taina; Salminen, Marika; Irjala, Kerttu; Viljanen; Anna; Koivula; Marja-Kaisa: Pulkki; Kari; Viitanen, Matti; Vahlberg, Tero; Viikari, Laura (Elsevier B.V., 2025)
Background: Cardiac troponin T (cTnT) and N-terminal B-type natriuretic propeptide (proBNP) are mainly used as biomarkers to diagnose specific conditions of the heart, but they also have predictive ability. Our aim was to study their associations with cardiovascular and all-cause mortality in an older population in non-acute conditions.
Methods: A population-based study with a ten-year follow-up. The data comes from a community-based representative sample of an older population with 1260 participants (participation rate 82 %). Associations were analyzed using Cox proportional hazard models.
Results: Altogether, 467 (37%) subjects died during the 10-year follow-up period, and 149 of those of a cardiovascular disease. Both elevated cTnT and proBNP concentrations were statistically significantly associated with cardiovascular and all-cause mortality in older adults.
Conclusions: Our study shows that older population with higher cTnT and proBNP concentrations have an increased risk of cardiovascular and all-cause mortality. Acknowledging the elevated risk may aid in targeting follow-up, prevention, and treatment adequately and more individually.